A study on competence and enrichment of virtualization in cloud computing - V. Anbazhagu, U; Maheshwaran, P; S. Archana, K; Gowr, Sheela (International Journal of Engineering and Technology, 2018)
The aim of this research is to study and enhance the applications of most profitable technology in cloud computing ever "Virtualization". Back then, a 15 years before, nobody knows about the technology named cloud computing exists. But now, every technology such as personal computer, mobile phone, tablet PC, even televisions rely on cloud computing. Cloud computing helps greatly in reducing costs, scalability and flexibility in computer services. Virtualization is the technologyÂ that helps cloud computing to emerge in a large profitable level. Using virtualization (such as server, network and storage virtualization technologies), the resource cost is reduced in great level.Â